A novel combinatorial strategy using Seliciclib (R) and Belinostat (R) for eradication of non-small cell lung cancer via apoptosis induction and BID activation - Ong, Pei-Shi (ELSEVIER IRELAND LTD, 2020)
10.1016/j.canlet.2016.07.023